DESAIN INFOGRAFIS PENDIDIKAN KARAKTER MENGGUNAKAN CANVA SEBAGAI MEDIA LITERASI DIGITAL - Rahmatila Djafar; Geyristha Pakaya (Journal of Community Services on Multidisciplinary Sciences, 2025)
This community service aims to enhance character education among elementary and middle school students through the design of infographics using Canva as a digital literacy medium. In the digital era, children and adolescents are exposed to various information that can influence their character development. Research shows that effective character education can help shape good personalities and reduce negative behaviors. By involving students, teachers, and parents in the planning and implementation process, this program is expected to create engaging and interactive learning materials. The results of this community service indicate an improvement in students' understanding of character values as well as their digital skills. This program is anticipated to be implemented in other schools to expand its positive impact.